Kinetics of the anodic dissolution of iron in concentrated ionic media : Galvanostatic and potentiostatic measurements - Podestá, José J. (1965)
The anodic dissolution of iron has been studied in concentrated aqueous media by determining potential/current curves using potentiostatic and galvanostatic techniques. The results indicate that the most likely value of Tafel slope in the range of pH from 0 to 5 is 2·3 (2RT/3F) for the anodic reaction. The agreement between the two techniques is good. Among the various mechanisms proposed for the reaction, the results are interpreted satisfactorily by means of the reaction scheme recently proposed by Bockris et al.